Economic evaluation of the cost of different methods of retesting chlamydia positive individuals in England. Issue 3 (23rd March 2019) - Looker, Katharine J; Buitendam, Erna; Woodhall, Sarah C; Hollis, Emma; Ong, Koh-Jun; Saunders, John M; Dunbar, Kevin; Turner, Katherine M E
Abstract : Objectives: The National Chlamydia Screening Programme (NCSP) in England opportunistically screens eligible individuals for chlamydia infection. Retesting is recommended three3 months after treatment following a positive test result, but no guidance is given on how local areas should recall individuals for retesting. Here, we compare cost estimates for different recall methods to inform the optimal delivery of retesting programmes. Design: Economic evaluation. Setting: England. Methods: We estimated the cost of chlamydia retesting for each of the six most commonly used recall methods in 2014 based on existing cost estimates of a chlamydia screen. Proportions accepting retesting, opting for retesting by post, returning postal testing kits and retesting positive were informed by 2014 NCSP audit data. Health professionals 'sense-checked' the costs. Primary and secondary outcomes: Cost and adjusted cost per chlamydia retest; cost and adjusted cost per chlamydia retest positive. Results: We estimated the cost of the chlamydia retest pathway, including treatment/follow-up call, to be between £45 and £70 per completed test. At the lower end, this compared favourably to the cost of a clinic-based screen. Cost per retest positive was £389–£607. After adjusting for incomplete uptake, and non-return of postal kits, the cost rose to £109–£289 per completed test (cost per retest positive: £946–£2, 506). The most economical method in terms of adjusted cost per retest was no active recall as gains in retest rates with active recall did not outweigh the higher cost. Nurse-led client contact by phone was particularly uneconomical, as was sending out postal testing kits automatically. Conclusions: Retesting without active recall is more economical than more intensive methods such as recalling by phone and automatically sending out postal kits. If sending a short message service (SMS) could be automated, this could be the most economical way of delivering retesting. However, patient choice and local accessibility of services should be taken into consideration in planning.